Simulator vožnje vozila pri mejnem zdrsu - Veber, Boštjan (Strojniški vestnik, 2003)
To qualify professional drivers for critical driving conditions, like rain, snow, and slippery ice, a skidding simulation is required. Using a skidding simulator it is possible to control the traction force of a vehicle. The traction force can be reduced by decreasing the normal force between the vehicle's wheels and the ground by lifting the vehicle's wheels, while the friction coefficient remains unchanged. In order to control the skidding simulator a new control system for the simulator was introduced. The system isbased on measuring the normal force. This paper presents the design solutions for the individual parts of the simulator.
Keywords: simulatorji vožnje; zdrsavanje vozil; krmiljenje zdrsa; rešitve konstrukcijske; zdrs; simulacija; modeliranje